A Novel Communication-Free Control Method for Eliminating DC Microgrid Shortcoming - Dhafer Mayoof Dahis (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
High voltage deviation, State of charge (SOCs) divergence, and inappropriate load/power sharing are some challenges that DC microgrids face. These problems can be rectified easily if the control algorithm is designed based on the other units' data. However, utilization of communication links has some disadvantages which make them improper in many cases. Regarding that, in this paper, a novel communication-free control method is presented. In this method, the droop gain is divided into two parts. The first part of the droop gain is selected according to the line resistance in such a way, that the effect of line resistance on current sharing is omitted, while the second part is considered for balancing SOCs. Regarding that, it is defined as a function of SOC such that the higher SOC unit injects more and absorbs less current. Comparing the simulation results of the proposed method with other methods proves that the proposed method can balance SOCs and reduce the DC bus voltage deviation like the SOC-based method. Besides, it can share current properly like the virtual resistance method.